1983
DOI: 10.1002/j.1460-2075.1983.tb01720.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo transcription of a eukaryotic regulatory gene.

Abstract: The PPR1 gene encodes the positive regulator of the URA1 and URA3 genes in yeast. Its transcription product is a 2.9‐kb polyadenylated RNA with an extremely short half‐life of 1 min. The induced or non‐induced cell contains approximately 0.1 molecules of PPR1 RNA, a constitutive level which is not altered by changing the number of structural genes to be regulated. The DNA sequence of a 399‐bp AccI‐Bg/II fragment including 180 nucleotides of the 5′‐flanking region of the gene PPR1 has been determined. By S1 map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 23 publications
(21 reference statements)
2
21
0
Order By: Relevance
“…With several bicistronic viral mRNAs, the (poly)peptide encoded in the upstream (mini)cistron has been detected (17,22,25,69), confirming that the leader sequence is indeed translated. In a few cellular mRNAs, the upstream ORF terminates very close to the ATG codon that initiates the major ORF (10,24,42,59,66); I would expect such mRNAs to reinitiate inefficiently, by analogy with the constructs described in Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With several bicistronic viral mRNAs, the (poly)peptide encoded in the upstream (mini)cistron has been detected (17,22,25,69), confirming that the leader sequence is indeed translated. In a few cellular mRNAs, the upstream ORF terminates very close to the ATG codon that initiates the major ORF (10,24,42,59,66); I would expect such mRNAs to reinitiate inefficiently, by analogy with the constructs described in Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
“…Sherman and Stewart (62) concluded from their study of cytochrome c mutants that yeast ribosomes cannot reinitiate, but in all of their mutants the upstream minicistron terminated very close to the ATG triplet that would have been used to reinitiate cytochrome c. That motif might be unfavorable for reinitiation in yeast, as it is in higher eucaryotes. Since upstream ATG codons, invariably followed by a terminator codon, have been found in a number of yeast mRNAs (18,24,42,50,56,66,67), it seems likely that yeast ribosomes either reinitiate or undergo leaky scanning, but neither mechanism has yet been established experimentally in yeast.…”
Section: Discussionmentioning
confidence: 99%
“…Culbertson, and A. Jacobson, in prep.). PPR1 encodes an inherently unstable mRNA (Losson et al 1983), which we have shown is stabilized by loss of UPF1 function (S.W. Peltz, P. Leeds, M.R.…”
Section: Genes and Developmentmentioning
confidence: 99%
“…The leader region of the transcript contains two contiguous AUG codons, followed by a stop codon, three codons later (Losson et al 1983). Therefore, it may contain a premature stop codon that normally targets the mRNA for degradation by the UPFl-mediated pathway.…”
Section: Genes and Developmentmentioning
confidence: 99%
“…A further modification of the scanning model of translation initiation states that 40s ribosomal subunits may bypass AUG codons if they do not exist in an optimal sequence context (Kozak, 1984;Losson et al, 1983). The results reported here would tend to support this model since for the A,, serotype which possesses a favourable initiation site for P20a a significant amount of this protein is synthesized.…”
Section: B E C L a R K E A N D Othersmentioning
confidence: 61%